"The Iranian Food Consumption Program (IFCP), A Unique Nutritional Software in Iran" - M Rafiei; M Boshtam; A Marandi; A Jalali; R Vakili (Tehran University of Medical Sciences, 2002)
The Iranian Food Consumption Program (IFCP), a unique program in Iran was developed to aim accurate calculation of nutrient intakes in relation to heart health investigation released in Isfahan Cardiovascular Research Center in March 1998 for the first time. The new versions came out along changes in computer technology. This interview-based program is designed to gather data through designed questionnaires in two dietary and non-dietary parts under an individual code number for each subject. The interview can be repeated to nine times for each code number. The non-dietary questionnaires are used to obtain information about personal, demographic and anthropometric characteristics, lipid profiles, personal and family history for cardiovascular disease and its risk factors, fasting blood sugar, blood pressure and heart rate records as well as physical activity data. The dietary data collection is flexibility programmed to be able to match easily with different methods of nutrition assessment especially record-assisted 24-hour recall method. A photographic food atlas makes food recalling accurate, easily and in real quantity and quality amounts. Therefore, a separate food list is made for each subject containing foods, ingredients and composed nutrients by record. Food analysis is performed to obtain daily nutrients intakes extremely accurate according to Iranian Food Table with over 1377 food items and values of 45 nutrients. The ultimate file can be exported in nearly eleven formats for statistical analysis. Consequently, the nutrient status can be easily investigated in designed studies for individuals, groups and populations especially concerning heart health. Also, the validity of the software was established by a comparative study through a trial and error. IFCP is useful for diet therapy, dietetic practice, nutrition research and epidemiological survey.